Bastidores e estreias: performers trans e boates gays abalando a cidade - Coelho, Juliana Frota da Justa (2009)
This paper interpellates the performances of transformists, transvestites and drag queens in the gay nightclubs of Fortaleza, more specifically, the nightclub Divine, located in the city downtown. In such places, the binary definition of male-masculine and female-feminine is deconstructed, bringing gender configurations that can be considered by many people as abjects. Willing to critically approach this theme, a discussion was initially made about the naturalizing construction standards of gender and sexuality through theories that deconstruct these very standards, as the queer studies, for example. The relation of the capital city of Ceará with those establishments that carry out this kind of spectacles dialogues with the Urban Anthropology, in a time interval that initiates in the beginning of the seventies and goes until the current days. The biographical narratives of performers and other people who exert important functions in this context also contribute to the understanding of the range the “trans spectacles” in the singularities of each experience. Finally, the aspects of subversion and/or legitimacy of these performances is questioned.